2014
DOI: 10.1038/ejhg.2014.115
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous germline mutations in A2ML1 are associated with a disorder clinically related to Noonan syndrome

Abstract: Noonan syndrome (NS) is a developmental disorder characterized by short stature, facial dysmorphisms and congenital heart defects. To date, all mutations known to cause NS are dominant, activating mutations in signal transducers of the RAS/ mitogen-activated protein kinase (MAPK) pathway. In 25% of cases, however, the genetic cause of NS remains elusive, suggesting that factors other than those involved in the canonical RAS/MAPK pathway may also have a role. Here, we used family-based whole exome sequencing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 28 publications
2
60
0
3
Order By: Relevance
“…For two frameshift variants, rs144686314 and rs143864957, there are 151 and 19 homozygous carriers in ExAC, respectively. Vissers et al hypothesised a dominant, activating effect of de novo missense variants in A2ML1 as the underlying mechanism, which might lead to Noonan syndrome in their patients 5. We deem it unlikely that the observed homozygous stop variant in our patient was responsible for the observed phenotype and the ACMG guidelines3 classify it as a variant of unknown significance.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…For two frameshift variants, rs144686314 and rs143864957, there are 151 and 19 homozygous carriers in ExAC, respectively. Vissers et al hypothesised a dominant, activating effect of de novo missense variants in A2ML1 as the underlying mechanism, which might lead to Noonan syndrome in their patients 5. We deem it unlikely that the observed homozygous stop variant in our patient was responsible for the observed phenotype and the ACMG guidelines3 classify it as a variant of unknown significance.…”
Section: Resultsmentioning
confidence: 63%
“…Two were premature stop mutations in A2ML1 and PLVAP. A2ML1 codes for alpha-2-macroglobulin-like 1 and has been discussed in the context of Noonan syndrome, but all variants were classified as variants of unknown significance because their contribution to Noonan syndrome could not be confirmed 5. Copy number variants and heterozygous rare variants in A2ML1 have also been described to be associated with otitis media in children 6.…”
Section: Resultsmentioning
confidence: 99%
“…A2ML1, which encodes the secreted protease inhibitor α-2-macroglobulin (A2M)-like-1, activates mutations in signal transducers of the RAS/mitogen-activated protein kinase (MAPK) pathway34. FZD9 19 encodes WNT receptors and is an important factor affecting WNT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Vissers et al 43 performed trio exome sequencing and identified a de novo variant (p.R802H) of A2ML1 in an individual with NS. Additional analyses of 155 individuals revealed missense variants (p.R592L and p.R802L) of A2ML1 in two families with NS.…”
Section: A2ml1mentioning
confidence: 98%